Coronary Artery Fistula: A Diagnostic Dilemma - Rajesh Kumar; Jathinder Kumar; Cormac O’Connor; Ihsan Ullah; Benjamin Tyrell; Ian Pearson; Sajjad Matiullah; Kevin Bainey (Interventional Cardiology: Reviews, Research, Resources)
Coronary artery fistula (CAF), although one of the rare coronary anomalies, is becoming increasingly more detectable in the recent years due to advancements in cardiac diagnostic imaging. Its long-term prognostic implications and importance for the cardiovascular system remain a dilemma for cardiologists and patients. Based on a variety of haemodynamic symptoms and complications, cardiologists must be aware of the characteristics of CAF and the diagnostic importance of multi-slice CT in evaluation, pre-procedural management and follow-up. Both surgical and percutaneous options are available for symptomatic patients or those with complications, while management of asymptomatic CAF remains a viable alternative.